2000
DOI: 10.1038/sj.ijir.3900604
|View full text |Cite
|
Sign up to set email alerts
|

The role of intraoperative antibiotic irrigation and postoperative antibiotic therapy for contaminated implantable prosthesis: in a rat model in vivo

Abstract: The aim of this study was to determine the usefulness of intraoperative antibiotic irrigation solution and long-term effective antibiotic therapy for the infected prostheses.Forty-®ve male Wistar albino rats were divided into three equal groups and a small piece of silicone prosthesis contaminated with Staphylococcus epidermidis was implanted into the scrotum. In the ®rst group, the silicone pieces were irrigated with an antibiotic solution intraoperatively and antibiotic therapy was applied for 20 days postop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…In the study, these rats also showed typical skin lesions and purulent scrotal discharge, indicating clinical infection due to S. epidermidis. 16 We did not observe such findings during the study in any groups.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In the study, these rats also showed typical skin lesions and purulent scrotal discharge, indicating clinical infection due to S. epidermidis. 16 We did not observe such findings during the study in any groups.…”
Section: Discussionmentioning
confidence: 60%
“…The rat model is apparently useful for investigating prosthesis infection and culture with respect to a similar study that was carried out before. 16,17 The aetiology of late prosthesis infection is still controversial. The effect of haematogenous seeding has been presented by many authors but not proven yet.…”
Section: Discussionmentioning
confidence: 99%
“…Both injection and irrigation were found to reduce S . epidermidis growth over 20 days, ranging from 86.7% in the control group to 33.3% in the systemic treatment group and 13.3% in the irrigation treatment group ( 22 ). However, it is important to note that as appreciation of antibiotic stewardship evolves, recent clinical studies have argued against postoperative antibiotics unless particular risk factors are identified, as the benefits to their use are limited ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…The value of aggressive intraoperative antibiotic irrigation during savage of clinically infected penile prostheses has been shown clearly [17,18]. Studies also have demonstrated that infections in prostheses contaminated with Staphylococcus epidermidis can be nearly eliminated with the use of intraoperative device irrigation [30].…”
Section: Infection Preventionmentioning
confidence: 98%